A teaching games for understanding program to deal with reasons for dropout in under-11 football - Barquero-Ruiz, C.; Morales-Belando, M. T.; Arias-Estero, J. L. (Research Quarterly for Exercise and Sport, 2021)
Young players report that they dropout of organized football due to excessive emphasis on technical execution, low success, and the lack of autonomy and motivation experienced by players during training sessions.